1998
DOI: 10.1159/000026532
|View full text |Cite
|
Sign up to set email alerts
|

A History of the Use of Anticonvulsants as Mood Stabilizers in the Last Two Decades of the 20th Century

Abstract: Anticonvulsants have moved into an important position as alternatives and adjuncts to lithium carbonate in the treatment of bipolar illness. Work with the nonhomologous model of kindled seizures helped in the choice of carbamazepine as a potential mood stabilizer and in the study of the mechanisms of action of the second generation anticonvulsants carbamazepine and valproate, as well as the putative third generation psychotropic anticonvulsants lamotrigine and gabapentin. Anticonvulsant neuropeptides such as T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 61 publications
(69 reference statements)
0
32
0
3
Order By: Relevance
“…The rationale for this indication is based on the utility of anticonvulsant medications as mood stabilizers and antidepressants in mood disorders (Goodwin and Jamison 1990;Post et al 1998;Calabrese et al 1999), the anticonvulsant properties of electroconvulsive therapy (ECT) (Sackeim et al 1983;Sackeim 1999), reports of improved mood, independent of seizure control, in epilepsy patients receiving VNS (Elger et al 2000;Harden et al 2000), the evidence from animal and human research that VNS results in altered concentrations of neurotransmitters implicated in mood disorders, including serotonin, norepinephrine, gamma aminobutyric acid, and glutamate (Ben-Menachem et al 1995;Krahl et al 1998;Walker et al 1999), and brain imaging findings that acute VNS results in modulation of functional activity in widespread cortical and subcortical brain regions ; see George et al 2000a,b for reviews).…”
mentioning
confidence: 99%
“…The rationale for this indication is based on the utility of anticonvulsant medications as mood stabilizers and antidepressants in mood disorders (Goodwin and Jamison 1990;Post et al 1998;Calabrese et al 1999), the anticonvulsant properties of electroconvulsive therapy (ECT) (Sackeim et al 1983;Sackeim 1999), reports of improved mood, independent of seizure control, in epilepsy patients receiving VNS (Elger et al 2000;Harden et al 2000), the evidence from animal and human research that VNS results in altered concentrations of neurotransmitters implicated in mood disorders, including serotonin, norepinephrine, gamma aminobutyric acid, and glutamate (Ben-Menachem et al 1995;Krahl et al 1998;Walker et al 1999), and brain imaging findings that acute VNS results in modulation of functional activity in widespread cortical and subcortical brain regions ; see George et al 2000a,b for reviews).…”
mentioning
confidence: 99%
“…The subsequent demonstration of carbamazepine's optimal usefulness against amygdala vs. cortical-kindled seizures [229], and the development of the kindling model of recurrent affective illness by Post, led to a more systematic investigation of its efficacy in recurrent affective disorders. Ballenger and Post reported the first controlled studies of carbamazepine efficacy in acute mania [230] in 1978, after which a number of studies have replicated this finding [23].…”
Section: Carbamazepinementioning
confidence: 99%
“…In 1968 Dehing reported that carbamazepine decreased aggression in some chronic psychiatric patients [225]. However, carbamazepine's efficacy in complex partial seizures of the temporal lobe, its positive psychotrophic profile in patients with such seizure disorders [226], the wealth of data implicating limbic dysfunction in disorders of affect, its antiaggressive effects, and the fact that it was a CNS-penetrant agent which reduced neuronal excitability led to its use as a potential antimanic agent [23]. The clinical efficacy of carbamazepine in the treatment of acute mania was first reported by Takezaki and Hanaoka (1971) in a small open trial [227], followed by a larger open trail by Okuma and colleagues (1975) [228].…”
Section: Carbamazepinementioning
confidence: 99%
See 1 more Smart Citation
“…Após sua administração crônica, ela demonstrou efeitos noradrenérgicos, dopaminérgicos e moduladores do sistema GABAérgico, que aumentaram os níveis de GABA no cérebro e no liquor. No entanto, não se sabe como a carbamazepina atuaria nos transtornos do humor (Post et al, 1998).…”
Section: Carbamazepinaunclassified